2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28717
|View full text |Cite
|
Sign up to set email alerts
|

On the Exploration of Game-Based Learning in STEM Education with the Development and Application of Virtual Reality Course Modules

Abstract: Game-Based-Learning is a powerful pedagogy that can effectively motivate and engage students in studying. With specifically designed computer games, Game-Based Learning (GBL) can create an enjoyable and engage learning experience for students. The emerging Virtual Reality (VR) technology in recent years can significantly improve such learning experience. In this paper, we present our GBL practice in STEM education through the development and integration of VR-based GBL modules into the engineering curriculum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The final goal was the assessment of the improvement perception in learning trends, through students' opinion on the specific teaching strategy adopted (CWL). Other researches adopted the GBL approach (Zhao et al, 2018), also through LAVR (Zhang et al, 2017), for serious games development. Students' familiarity with computer games improves engagement and enjoyment for improved learning performances.…”
Section: Introductionmentioning
confidence: 99%
“…The final goal was the assessment of the improvement perception in learning trends, through students' opinion on the specific teaching strategy adopted (CWL). Other researches adopted the GBL approach (Zhao et al, 2018), also through LAVR (Zhang et al, 2017), for serious games development. Students' familiarity with computer games improves engagement and enjoyment for improved learning performances.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying that neural network models capture better insight during learning for system deployment was key in creating a heterogeneous approach. This approach was developed to investigate accuracy, structure, and target prediction methods to address complexity by simplifying different features [4] [2].…”
Section: Methodsmentioning
confidence: 99%
“…As an educational tool, virtual reality has been show to be an effective tool in both K-12 and higher education 9 . In addition, it has been shown that games based in virtual reality can improve the learning experience in users 13 .…”
Section: Introductionmentioning
confidence: 99%